(3TQM GdTeSjIs - (3eLghds ((3LeGd GdOjf Hf Ydj NGf GdfXfRjs)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI, hLO YHGQI GdeJf aj cKjQ ef GdfSN hGdUhGH Gf daXI KdGK ggfGs
(3BNQgG (B:s
(3BNQgG(B: (3ceG jMce Ydi ZjQ GdeMShS bjGSG Ydi GdeMShS hbHd cd ehLhO EeG LSe Ch MGd ajg hGdYeOI (B.. (3GdePchQI gh GdHQgGf dCfg gh GdehUd Edi GdJUOjb GdcGed GdJj hUdJ Edi eQJHI Gdjbjf hdfNJe cJGHfG Ydi Gdjbjfs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs